Pengaruh PDRB Per Kapita, Investasi Dan Belanja Modal Terhadap Kemandirian Keuangan Daerah Kabupaten dan Kota Di Provinsi Jawa Barat Tahun 2020-2023 - Totoh Abdulfatah; Sri Mulyani (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
Regional Financial Independence is an indicator of a region that is able to implement regional autonomy without depending on transfer funds from the Central Government. West Java Province is one of the province that implements the principle of fiscal decentralisation. However, the Regency / City in West Java Province still experience inequality between regions. This study aims to examine empirically the effect of GRDP per capita, investment and capital expenditure on regional financial independence. Capital Expenditure on regional financial independence with a sample of 27 regencies / cities in West Java Province.in West Java Province. This research is quantitative research using secondary data using secondary data. The research method used is the Fixed Effect Model (REM). GRDPPer Capita, Investment and Capital Expenditure together have an influence oninfluence on Regional Financial Independence. GRDP per capita has a positive effectsignificant effect on regional financial independence, investment has no effect on regional financial independence, while capital expenditure has a negative effect on regional financial independence on regional financial independence, while capital expenditure has a negative and significant effect on regionalfinancial independence significant on regional financial independence.